Chemsex and HIV/AIDS: Strategies for Harm Reduction and Education - Muhammad Suleman; Muhammad Ashraf (Indus Journal of Bioscience Research, 2023)
Chemsex, the practice of using drugs in a sexual context, has gained prominence in recent years, particularly among men who have sex with men (MSM). This paper explores the complex relationship between chemsex and the transmission of HIV/AIDS. It delves into the socio-cultural factors contributing to the rise of chemsex, the associated risks of HIV transmission, and the role of harm reduction and education in mitigating these risks. Drawing from existing research and case studies, this paper presents a comprehensive analysis of chemsex-related HIV/AIDS concerns and proposes evidence-based strategies for harm reduction and education.